Effect of phosphorus and potassium on yield and on agronomical characteristics of cotton - Staut, Luiz Alberto; Athayde, Manoel Luiz Ferreira (Pesquisa Agropecuaria Brasileira, 1999)
With the objective of studying the effect of increasing phosphorus and potassium doses on the agronomical and technological characteristics of the cotton (Gossypium hirsutum L.), cultivar IAC 20, an experiment was carried out during 1994/95 on a Red-Dark Latossol at the Embrapa-Centro de Pesquisa Agropecuária do Oeste (CPAO) in Ponta Porã, MS, Brazil. A randomized bloch design was used in a 3 x 5 factorial arrangement with four replications. The doses were 30, 60 and 90 kg ha-1 of P2O5, applied as triple superphosphate, and 0, 30, 60, 90 and 120 kg ha-1 of K2O as KCl. The K2O doses used had a significant influence on the seed cotton yield, plant height and weight of 100 seeds and of bolls.